FN-modulation loop architecture for fully integrated 1 Mb/s GFSK transmitter - Märzinger, Günther; Springer, Andreas; Weigel, Robert; Herzinger, Stefan; Fenk, Josef (IEEE MTT-S Microwave Symposium, 1999)
A low cost GFSK transmitter architecture is investigated for its sensitivity to parameter variation in mass production. In this paper the simulation results for a system design, based on certain specifications, are presented and the effects of mismatch in the open loop gain are demonstrated. It is shown that the system specifications can be met if the open loop gain error is less than 8% of the nominal value
elib2cris::1512001600,maerzinger1999